Improving the Moral Development of Children Aged 5 – 6 Years Through Method Played - Imam Tabroni; Ani Suarni (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the method of playing on the moral development of children. The research was conducted using a qualitative approach to direct field studies. The data collection of theoretical studies uses books related to this material. Data were analyzed using descriptive narrative. The results showed the role of the play method on the moral development of children. Playing can encourage children to have the ability to express and control emotions, empathy, fairness, do not discriminate in making friends, have an awareness of rights and responsibilities and be able to respect the ways of thinking of other people who are different from themselves, here children also learn manners such as saying say please when asking for help, say sorry if you make a mistake and say thank you if you get something from someone else. The type of game that plays the most role in improving children's moral development is role playing. The results of the study imply for parents, educators and caregivers to always provide game stimulation to children so that their moral development increases.